COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN DESA WISATA KALIWLINGI DI KABUPATEN BREBES - Imtiyaza, Hana; Sunu Astuti, Retno; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Brebes Regency has diverse and good natural tourism potential that needs to be developed to become an economic driver, one of which is through tourist villages. Kaliwlingi Tourism Village is one of the iconic tourism destinations in Brebes Regency with its mangrove forest ecosystem, where this tourism combines natural, social and cultural elements as a distinctive characteristic and local wisdom. The development of the Kaliwlingi Tourism Village already has a clear legal basis, guided by Regional Regulation Number 11 of 2021. In its implementation, the development of the Kaliwlingi Tourism Village applies a collaborative governance strategy involving several stakeholders. The aim of this research is to analyze the Collaborative Governance process in developing the Kaliwlingi Tourism Village in Brebes Regency and analyze the inhibiting factors. The analysis uses the Collaborative Governance theory from Ansell & Gash and the theory of inhibiting factors for Collaborative Governance from Mattessich & Monsey. This research uses a qualitative descriptive method. Data collection was carried out through observation, interviews and documentation techniques. The research results show that Collaborative Governance in the development of the Kaliwlingi Tourism Village, which includes face-to-face dialogue, building trust, commitment to the process and mutual understanding, has not been implemented optimally. The inhibiting factors in the collaboration process are membership, structure, communication and resources.